2013
DOI: 10.1371/journal.pone.0059540
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ice Growth and Recrystallization by Zirconium Acetate and Zirconium Acetate Hydroxide

Abstract: The control over ice crystal growth, melting, and shaping is important in a variety of fields, including cell and food preservation and ice templating for the production of composite materials. Control over ice growth remains a challenge in industry, and the demand for new cryoprotectants is high. Naturally occurring cryoprotectants, such as antifreeze proteins (AFPs), present one solution for modulating ice crystal growth; however, the production of AFPs is expensive and inefficient. These obstacles can be ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 55 publications
(79 reference statements)
0
66
0
Order By: Relevance
“…The control of ice nucleation is essential to engineer the porous morphology of the scaffolds. The antifreezing substances such as anti freezing proteins and salts like zirconium acetates are the important class of materials which controls the ice nucleation by the exposure of hydrophobic residues on ice nuclei (Duman, 2015;Mizrahy, Dolev, Guy, & Braslavsky, 2013). The pore structure is mainly controlled by the ice nucleation, which is influenced by various parameters such as solution viscosity, concentration of the solute, growth velocity of ice crystals and pH.…”
Section: Results and Discussion 31 Scanning Electron Microscopymentioning
confidence: 99%
“…The control of ice nucleation is essential to engineer the porous morphology of the scaffolds. The antifreezing substances such as anti freezing proteins and salts like zirconium acetates are the important class of materials which controls the ice nucleation by the exposure of hydrophobic residues on ice nuclei (Duman, 2015;Mizrahy, Dolev, Guy, & Braslavsky, 2013). The pore structure is mainly controlled by the ice nucleation, which is influenced by various parameters such as solution viscosity, concentration of the solute, growth velocity of ice crystals and pH.…”
Section: Results and Discussion 31 Scanning Electron Microscopymentioning
confidence: 99%
“…In theory, both PVA (Knight et al, 1995) and ZrA/ ZrAH (Mizrahy et al, 2013) mimic the structure of the ice-binding domain found in naturally occurring AFPs for ice crystal recognition. The mode of action found in these chemical alternatives is likely different from AFPs, because both substances can create gel-like phases that are able to envelope ice crystals.…”
Section: Chemical Alternatives To Afpmentioning
confidence: 94%
“…Initially, recrystallization was not given much attention in the context of AFPs, but more recentlydand especially in relation to AFPs as an additive to fooddit has become an important factor in research (Zhang et al, 2007a,b;Regand and Goff, 2006;Crilly et al, 2008;Hightower et al, 1991;Mizrahy et al, 2013).…”
Section: Recrystallizationmentioning
confidence: 99%
See 2 more Smart Citations